Methylation status of the APC and RASSF1A promoter in cell-free circulating DNA and its prognostic role in patients with colorectal cancer - MATTHAIOS, DIMITRIOS (Oncol Lett, 2016)
DNA methylation is the most frequent epigenetic alteration. Using methylation-specific polymerase chain reaction (MSP), the methylation status of the adenomatous polyposis coli (APC) and Ras association domain family 1 isoform A (RASSF1A) genes was examined in cell-free circulating DNA from 155 plasma samples obtained from patients with early and advanced colorectal cancer (CRC). APC and RASSF1A hypermethylation was frequently observed in both early and advanced disease, and was significantly associated with a poorer disease outcome. The methylation status of the APC and RASSF1A promoters was investigated in cell-free DNA of patients with CRC. Using MSP, the promoter methylation status of APC and RASSF1A was examined in 155 blood samples obtained from patients with CRC, 88 of whom had operable CRC (oCRC) and 67 had metastatic CRC (mCRC). The frequency of APC methylation in patients with oCRC was 33%. Methylated APC promoter was significantly associated with older age (P=0.012), higher stage (P=0.014) and methylated RASSF1A status (P=0.050). The frequency of APC methylation in patients with mCRC was 53.7%. In these patients, APC methylation was significantly associated with methylated RASSF1A status (P=0.016). The frequency of RASSF1A methylation in patients with oCRC was 25%. Methylated RASSF1A in oCRC was significantly associated with higher stage (P=0.021). The frequency of RASSF1A methylation in mCRC was 44.8%. Methylated RASSF1A in mCRC was associated with moderate differentiation (P=0.012), high levels of carcinoembryonic antigen (P=0.023) and methylated APC status (P=0.016). Patients with an unmethylated APC gene had better survival in both early (81±5 vs. 27±4 months, P<0.001) and advanced disease (37±7 vs. 15±3 months, P<0.001), compared with patients with methylated APC. Patients with an unmethylated RASSF1A gene had better survival in both early (71±6 vs. 46±8 months, P<0.001) and advanced disease (28±4 vs. 16±3 months, P<0.001) than patients with methylated RASSF1A. The observed significant correlations between APC and RASSF1A promoter methylation status and survival may be indicative of a prognostic role for these genes in CRC, which requires additional testing in larger studies.